PENGARUH CORPORATE SOCIAL RESPONSIBILITY, IT CAPABILITIES, DAN SUPERIOR PERFORMANCE TERHADAP ECONOMIC PERFORMANCE - Arry Eksandy; Anggi Alwid Putriawan (COMPETITIVE, 2020)
This study aims examine the effect of Corporate Social Responsibility, IT apabilities, and Superior Performance on the Economis Performance of manufacturing companies listed on the BEI in 2014-2018. This study use purposive sampling method. Based on the criteria, this study use sampling manufacturing company. The data this study is obtained from annual audited financial statements, subtainability repots and summary of company performance samples obtained from the Indonesia Stock Exchange website (www.idx.com). This study used panel regression model. This study found that overall the variables has an effect on economic performance, which partially Corporate Social Responsibility has positive effect to the Economic Performance, IT Capabilities has no effect to the Economic Performance and Superior Performance has positive effect to the Economic Performance.